Nutritional Composition of Meal Replacement Recipes for Body Weight Reduction Interventional Program (My Body is Fit and Fabulous at Work, MyBFF@Work) - Rosli , Wan; Haslina , Nor; Izani, Wan Mohd; Alina, Tengku (Universiti Sains Malaysia, 2018)
The development of meal replacement recipes is emphasized based on the replacement of white rice-based ingredient with non-white rice-based ingredient which commonly consumed among Malaysian. This study aimed to determine nutrient composition of fifty selected menu of replacement meal. Fifty selected menu of replacement meal were distributed to intervention group for six months at lunch break during working days. Analysis was conducted for the determination of protein, fat, carbohydrate and energy according to AOAC method. The prepared meals were then palatably tested by 10 untrained panelists who judged the appearance aroma, colour, flavour and overall acceptability. Nutrient content of meal were ranged from 3.8 to 43.3 g for fat, 5.8 to 47.4 g for protein and 40.0 to 106.6 g for carbohydrate. Energy values of these meals were in the range from 494.2 to 698.5 kcal. Creation of replacement meals may provide wider range of alternative menus to be chosen by any health professionals to plan their healthy diet plan. Individual and health conscious consumers can adopt these unique alternative recipes in preparing their routine meals for interventional program of body weight reduction.